Introducing real estate led start-up urbanism: An account from Greater Paris - Gomes, Pedro; Pérès, Yoann (Progress in planning, 2022)
•Real estate led start-up urbanism mixes urban development and innovation principles.•CIUPs are drivers of inter-organizational change within the planning system.•Real estate developers reorganize in face of increased demands for collaborative work.•Small operators and new consultancies seize opportunities to open up new markets.•Developers’ innovation strategies depend on their broader positioning in the market. In the past few years, calls for innovative urban projects (CIUPs) have become the most mediatized symbol of the ongoing transformations within the public-led French urban development system. In the name of urban innovation, CIUP is a policy instrument that brings together, early in the design phase of urban development projects, extended teams of real estate developers and other actors who usually intervene downstream in the development process. We explore these calls as a form of real estate led start-up urbanism and analyse its modalities in Greater Paris, with the first edition of the Inventing the Greater Paris Metropolis (IGPM) call as a case study. We begin by tracing the genealogy of CIUPs and their particular articulation of urban innovation and urban development principles. In the remainder of the paper, we explore the implications of such urban innovation and spatial planning hybrids, by honing in on the relational work of real estate developers, i.e. the production of social relationships and networks that enables real estate developers adherence to the political ambitions during the bidding process. After establishing their centrality in the social networks defined by IGPM, we explore the apparent paradox between projects that are perceived as ordinary by call organizers and a visible effervescence of the urban planning milieu, including recruitment practices within real estate development firms, the emergence of small operators embodying imaginaries of urban innovation and the growing role of consultancies in supporting developers in responding to public authorities’ ambitions. In the final empirical section of the paper, we focus on real estate developers’ innovation strategies as a way of understanding the apparent contradiction between project content and the changing organizational landscape of the urban development milieu. In the concluding section, we bring these elements together through a discussion of the policy outputs and outcomes of CIUPs in general, and of IGPM in particular.